Cost-effectiveness of cardio-oncology clinical assessment for prevention of chemotherapy-induced cardiotoxicity - de Mello-Sampayo, F.; Fiuza, M.; Pinto, F.; Fonte, J. (Revista Portuguesa de Cardiologia, 2021)
Introduction Cancer chemotherapy increases the risk of heart failure. This cost-effectiveness study analyzes cardio-oncology imaging assessment of left ventricular ejection fraction (LVEF) using a Portuguese healthcare payer perspective and a five-year time horizon. Methods Two cardioprotective strategies were assessed: universal cardioprotection (UCP) for all patients and cardioprotection initiated on diagnosis of LVEF-defined cardiotoxicity (EF-CTX). A Markov model, informed by the retrospective clinical course of breast cancer patients followed in a Portuguese public hospital, was developed to assess the cost-effectiveness of LVEF cardio-oncology imaging assessment. Data on transition probabilities, costs and utilities were retrieved from both the retrospective data and published literature to assess the cost-effectiveness of LVEF echocardiographic assessment. Costs and utilities of the cardioprotective strategies were assessed over a five-year range, using probabilistic sensitivity analyses. Results In the reference case of a 63-year-old breast cancer patient treated with cardioprotection initiated on diagnosis of EF-CTX, the five-year time horizon (4.22 QALYs and €2594 cost over five years) dominated UCP (3.42 QALYS and €3758 cost over five years). Under a time horizon of five years at a willingness-to-pay threshold of €22 986, over 65.7% of simulations provided additional QALYs. Monte Carlo simulation of the Markov model had no effect on the model's conclusions. Conclusion In the Portuguese public healthcare system and under specific hypotheses, from a healthcare payer perspective, EF-CTX-guided cardioprotection for patients at risk of chemotherapy-related cardiotoxicity provides more QALYs at lower cost than UCP.